Exploring Agency in the Construction of a Translated Character Narrative: A Multiple-Case Study on Early Sibelius-Related Translations into Finnish - Rautaoja, Turo (fi=Turun yliopisto|en=University of Turku|, 2023)
This dissertation explores the application of the sociological narrative theory in Translation Studies, with a focus on the Finnish translations of texts related to Finland’s national composer, Jean Sibelius. Drawing on Mona Baker and the scholars upon whom she bases her theory, the study first critically examines the premise of the approach and then aims to throw light upon how the theory can be used in the analysis of narratives focussing on an individual. For this purpose, particular attention is paid to translators’ agency and translatorship. In the dissertation, I conduct a multiple-case study on 12 Sibelius-related texts published in Finland and translated into Finnish from Swedish, English and German between 1916 and 1965. A three-part contextual framework is introduced to elucidate some of the relational settings from which the literary materials examined emerged and to provide an understanding of the overall literary genre of non-fiction texts. The texts are then studied with the help of various paratextual sources to uncover different narrative strands and the agencies involved in creating and promoting the nationally significant Sibelius narrative. The results of the study suggest that combining the sociological narrative theory in Translation Studies with agential considerations can provide valuable insights into the mechanisms of narrative construction and help to examine translators’ role in social developments that may have a considerable lifespan. At the same time, it acknowledges that further research into the underlying principles and history of the theory is needed to truly solidify the narrative approach as an academically viable option within Translation Studies. The findings of the study also suggest that questions concerning narrative construction extend beyond the technicalities and structural aspects of the building process. Based on the multiple-case study conducted, I argue that narrative construction needs to be considered more broadly if the aim is to gain a more comprehensive understanding of the narrative examined. KEYWORDS: translation, narrative theory, agency, translatorship

Väitöskirja tarkastelee käännöstieteessä sovellettua sosiologista narratiiviteoriaa ja keskittyy erityisesti Suomen kansallissäveltäjään, Jean Sibeliukseen, liittyviin suomeksi käännettyihin teksteihin. Tutkimus pohjautuu Mona Bakerin ja tämän hyödyntämien tutkijoiden teoreettisiin havaintoihin. Tutkimuksessa Bakerin lähestymistavan perusteita tarkastellaan ensin kriittisesti, minkä jälkeen tapaustutkimusten avulla selvitetään, miten teoriaa voidaan hyödyntää analysoitaessa yksilöön keskittyviä narratiiveja. Erityistä huomiota kiinnitetään kääntäjien toimijuuteen ja kääntäjyyteen. Väitöskirja sisältää tapaustutkimusten sarjan, jossa keskitytään tarkastelemaan 12:ta Sibeliukseen liittyvää vuosien 1916 ja 1965 välillä julkaistua ja suomeksi ruotsista, englannista ja saksasta käännettyä tekstiä. Tapauksia tarkastellaan suhteessa kolmiosaiseen kontekstuaaliseen kehykseen, joka valaisee niitä relationaalisia puitteita, joissa kirjalliset materiaalit syntyivät. Tämän jälkeen tekstejä tarkastellaan paratekstuaalisten lähteiden avulla pyrkimyksenä tunnistaa erilaisia narratiivijuonteita sekä kansallisesti merkittävän Sibelius-narratiivin luomiseen ja ylläpitämiseen vaikuttaneita toimijuuksia. Tutkimuksen tulosten perusteella esitän, että käännöstieteessä hyödynnetyn sosiologisen narratiiviteorian ja toimijuuden tarkastelun yhdistäminen voi tarjota arvokasta tietoa narratiivien rakentumisesta ja auttaa tutkimaan kääntäjien roolia pitkän aikavälin yhteiskunnallisissa kehityskuluissa. Tutkimus paljastaa myös, että narratiiviteorian taustaperiaatteet ja historia vaativat lisätutkimusta ja selvennystä, jos sen halutaan pysyvän elinvoimaisena osana käännöstiedettä. Tutkimuksen löydökset osoittavat, että narratiivien rakentumista koskevat kysymykset eivät rajoitu vain narratiivien synnyn mekaniikkaan ja teknisiin kysymyksiin. Tehtyjen tapaustutkimusten perusteella esitän, että narratiivien rakentumista on tarkasteltava laajemmalla perspektiivillä, jos tavoitteena on syvällinen ymmärrys tarkasteltavasta narratiivista. ASIASANAT: kääntäminen, narratiiviteoria, toimijuus, kääntäjyys